Delivery of the Posterior Arm as Initial Maneuver to Relieve Shoulder Dystocia Increased Neonatal Humeral Fractures [24D]. (May 2018) - Gold, Stacey; Hirsch, Daniel; Schutzman, David; Cohen, Arnold; Jaspan, David; Goldberg, Jay
Abstract : INTRODUCTION: Delivery of the posterior arm as the initial maneuver to relieve shoulder dystocia increased neonatal humeral fractures. To evaluate if institutionally adopting delivery of the baby's posterior arm as the initial maneuver during shoulder dystocia has increased the rate of neonatal humeral fractures. METHODS: In the beginning of 2011, Einstein Medical Center Philadelphia initiated a policy of attempting to deliver the posterior arm as the initial maneuver to resolve shoulder dystocia with the aim of decreasing brachial plexus injuries. Hospital databases were searched to identify deliveries complicated by neonatal humeral fractures, as well as other delivery information. Statistical analysis was performed. RESULTS: Between 2004 and 2010, 3 neonatal humeral fractures were identified from 13, 536 vaginal deliveries. Following initiation of the posterior arm policy, from 2011 through August of 2017, 31 humeral fractures were identified from 13, 750 vaginal deliveries. Almost all humeral fractures were associated with a shoulder dystocia. The rate of neonatal humeral fractures following the intervention increased by a factor of 10.8. The rate of humeral fracture pre- and post-intervention were compared with both Chi-squared test for independence and the Fisher's Exact Test with both p values < 0.000001. CONCLUSION: Initially attempting delivery of the posterior arm to resolve shoulder dystocia was associated with a significant increase in the rate of neonatal humeral fractures. Further study is warranted to determine if there was a decrease in the rate of brachial plexus injury to justify continuation of our current institutional management of shoulder dystocia.